Union Networks and Global Unionism in Maritime Shipping - Lillie, Nathan (Relations industrielles / Industrial Relations, 2005)
Under the auspices of the International Transport Workers’ Federation’s (ITF) Flag of Convenience campaign, maritime unions have developed transnational global structures exploiting interdependencies in transportation production chains. The ITF, a London-based association of transport unions, connects the struggles of seafarers and port workers through a global strategy of union networking and coordinated industrial action. Seafaring unions draw on the industrial leverage of port workers to negotiate minimum standard pay agreements, while dock unions leverage the growing influence of the ITF in fighting union busting in ports. A global transnational ship inspector network provides the power basis for imposing collective agreements on shipowners. Although conceived as a resource for organizing seafarers, the inspectorate also provides port unions with leverage.